2011
DOI: 10.1039/c1cc10357a
|View full text |Cite
|
Sign up to set email alerts
|

Size dependent macrophage responses and toxicological effects of Ag nanoparticles

Abstract: The immune-response of macrophages is an important area of investigation since it represents the major pathway by which early-stage defense barriers are established in skin, lungs, and mucosal systems to counteract foreign objects. In this study, we have examined the size-dependent inflammatory and toxicological effects of nanostructured silver particles (nano-Ag) on macrophage immune cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
139
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(147 citation statements)
references
References 25 publications
7
139
0
1
Order By: Relevance
“…Studies using various cell lines reported that Ag-NPs affected mitochondrial function and induced cell necrosis or apoptosis 24,25) . However, other investigators found no such cytotoxic effects of Ag-NPs on living cells 26) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using various cell lines reported that Ag-NPs affected mitochondrial function and induced cell necrosis or apoptosis 24,25) . However, other investigators found no such cytotoxic effects of Ag-NPs on living cells 26) .…”
Section: Discussionmentioning
confidence: 99%
“…their size, size distribution, shape, state of dispersion, physical and chemical properties, surface area and porosity, surface chemistry) and by cell characteristics (e.g. cell line, number of cells per well, and the period of culture before and/or after exposure to nanoparticles) 17,[24][25][26]29,30) . A recent study showed a decrease in MC3T3-E1 cell viability after exposure to Ag-NPs using the WST-8 assay 31) , but this study used different test conditions for cell culture and exposure to Ag-NPs, which may explain the disparity between their results and ours.…”
Section: Discussionmentioning
confidence: 99%
“…For example, phagocytosis has been believed for quite some time to be associated uniquely with the uptake of large particles (.1 mm). However, there are several reports that show the phagocytosis of nanometer-sized particles such as viruses (Clement et al 2006;Ghigo et al 2008), gold (Krpetic et al 2010;Franca et al 2011), silver (Park et al 2011), and polymer nanoparticles (Lunov et al 2011), as well as quantum dots .…”
Section: Sizementioning
confidence: 99%
“…Aflatoxin producers, A. parasiticus and A. flavus are therefore the most characterized fungal models for studying mycotoxin biosynthesis. The 20nm AgNps are model silver nanoparticles that have been used consistently for toxicity assays in several models [9]. In a previous fungal toxicity study, 0.05mg/L concentrations of 25nm AgNps have demonstrated effective inhibition of fungal growth [7].…”
mentioning
confidence: 99%